E-Clearing Obstacles to Banks Operating in Jordan: A Field Study - Daher, Ahmad (Jordan Journal of Business Administration, 2018)
This study aims to identify the obstacles of electronic clearing facing the banking sector in Jordan. The study also aims to identify the differences among respondents in terms of gender, age, experience, educational qualification and the age of the bank for which the respondent works. To achieve the study objectives, a questionnaire was designed and distributed to 80 employees at the bank clearing departments, where only 70 questionnaires were returned and found valid for statistical analysis (i.e., the response rate was 87.5%). The relevant statistical tests were performed and showed that some obstacles of electronic clearing for the banking sector in Jordan were found, including absence of foreign exchange clearing, frequent damage of electronic clearing equipment in banks and lack of clarity of the seals when checking the picture of the check, among other things. Moreover, the results of statistical analysis indicated that there are no statistically significant differences among the respondents in terms of gender, age, experience, educational qualification and the age of the bank for which the respondent works.